Crack propagation and fracture in silicon wafers under thermal stress. (23rd June 2013) - Danilewsky, Andreas; Wittge, Jochen; Kiefl, Konstantin; Allen, David; McNally, Patrick; Garagorri, Jorge; Elizalde, M. Reyes; Baumbach, Tilo; Tanner, Brian K.
<x xml:space="preserve">Abstract</x> The behaviour of microcracks in silicon during thermal annealing has been studied using in situ X‐ray diffraction imaging. Initial cracks are produced with an indenter at the edge of a conventional Si wafer, which was heated under temperature gradients to produce thermal stress. At temperatures where Si is still in the brittle regime, the strain may accumulate if a microcrack is pinned. If a critical value is exceeded either a new or a longer crack will be formed, which results with high probability in wafer breakage. The strain reduces most efficiently by forming (hhl) or (hkl) crack planes of high energy instead of the expected low‐energy cleavage planes like {111}. Dangerous cracks, which become active during heat treatment and may shatter the whole wafer, can be identified from diffraction images simply by measuring the geometrical dimensions of the strain‐related contrast around the crack tip. Once the plastic regime at higher temperature is reached, strain is reduced by generating dislocation loops and slip bands and no wafer breakage occurs. There is only a small temperature window within which crack propagation is possible during rapid annealing.